Optimizing Rapid Granulator Machines Utilization Using Overall Equipment Effectiveness and Capacity Measurement in Injection Molding - Hery Hamdi Azwir; Thomas Christian (Performa: Media Ilmiah Teknik Industri, 2021)
Low productivity can be affected by several conditions like machine downtime, operator performance, inefficient capacity planning, etc. The most effective way to find out the solution to this problem is to calculate machine utilization. The purpose of this research is to optimize Rapid Granulator machines in the injection molding area by using Day in the Life Of (DILO) observation, Overall Equipment Effectiveness (OEE), and capacity measurement. The research will analyze the suitable calculation metric to measure Rapid Granulator machines utilization by comparing machine capacity, planned run time, planned preventive maintenance, and the number of machines needed. In the last two years, the expected efficiency rate is always increasing up to 95% with the average of PT. MT Indonesia utilization rate of 85%. However, there are no standards or unified way to measure a machine’s utilization rate and due to the huge variety of machinery not all of them have the calculation metrics. Further observation shows that Rapid Granulator machines that located in the Injection Molding area of PT. MT Indonesia has never been calculated and the low utilization rate can be seen after a quick time study. A sample of 16 machines is measured with only 23% of utilization rate in one shift operation time. The result then shows that the improvement activities to reduce the number of machines from 105 to 24 will increase the utilization rate up to 87% with the OEE score increasing from 1.8% to 39%. Thus, PT. MT Indonesia can minimize cost as expected in the cost calculation and optimize Rapid Granulator machines usage.